Technology policy and the development of small and medium scale enterprises in contemporary Nigeria - Oladeji, S. I. (Technovation)
The author feels that Government intervention should be considered to be more effective than the development of local technological capability for the prosperity of SME's in Nigeria. Efforts are required in policy formulation and implementation.